The ophthalmic fallout in Utah after the Great American Solar Eclipse of 2017 - Ricks C; Montoya A; Pettey J (Clinical Ophthalmology, 2018)
Christopher Ricks,1 Alexandrea Montoya,2 Jeff Pettey1 1John A. Moran Eye Center, Salt Lake City, UT, USA; 2Department of Ophthalmology, University of Utah School of Medicine, Salt Lake City, UT, USA Background: Solar retinopathy is a rare ophthalmic disorder resulting from sustained viewing of the sun without protective eyewear. Incidence of solar retinopathy typically increases following a solar eclipse due to attempted visualization of the sun without appropriate eye protection. This paper serves as a case series of all available reported cases of solar retinopathy present in Utah resulting from the August 21st, 2017 solar eclipse. Methods: Twenty-seven patients had presented with concern for vision changes after the solar eclipse and six patients had exam findings consistent with solar retinopathy. Of these six cases, charts were available for three. Results: The common finding in all cases was a central scotoma with a correlating change to the inner segment/outer segment junction on optical coherence tomography. Demographically, all three patients were young males. Conclusion: This data provides insights on populations in Utah at risk for ophthalmic damage and can aid in targeting education programs in the future. Keywords: OCT, ophthalmology, retina, solar retinopathy, solar eclipse